ANALISIS PENGARUH KEPEMILIKAN MANAJERIAL, PROPORSI DEWAN KOMISARIS INDEPENDEN, DAN KONSERVATISME AKUNTANSI TERHADAP KUALITAS LABA SERTA PENGARUHNYA TERHADAP NILAI PERUSAHAAN - Sugianto, Shanty; Sjarief, Julianti (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2018)
This research aims to examine the effect beetween managerial ownership, proportion of independent commissioner, accounting conservatism towards earnings quality and firm value. In the first research model, managerial ownership, proportion of independent commisioner, accounting conservatism are the independent variables while earnings quality is the dependent variable. In the second research model, earnings quality is the independent variable and firm value is the dependent varible. Object of this research is manufacturing companies that are listed in Indonesian Stock Exchange (BEI) during 2014 to 2016. For the first research model there are 156 sampels and 273 sampels for the second research model. Hypotheses examination for the first research model using multiple linear regressions and for the second model using simpel linear regression with SPSS version 23.0. The result from the first research model shows managerial ownership and proportion of independent commissioner has no effect towards earnings quality, while accounting conservatism have an effect towards earnings quality. The result from the second research model shows that earnings quality has an effect towards firm value.